1999
DOI: 10.1007/s004250050665
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa and tobacco cells react differently to chitin oligosaccharides and Sinorhizobium meliloti nodulation factors

Abstract: Alfalfa (Medicago sativa L.) suspension cultures respond to yeast elicitors with a strong alkalinization of the culture medium, a transient synthesis of activated oxygen species, and typical late defence reactions such as phytoalexin accumulation and increased peroxidase activity. The alkalinization reaction as well as the oxidative burst were also observed when tobacco (Nicotiana tabacum L. ) cell-suspension cultures were treated with yeast elicitors. Depending on the degree of polymerization, N-acetyl chitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 35 publications
1
52
0
2
Order By: Relevance
“…Infection with Sinorhizobium meliloti wild-type strain Rm2011 was performed as described previously (Schenkluhn et al, 2010). S. meliloti NFs were isolated from a NF-overproducing strain of S. meliloti strain 1021 p(EK327) as described by Baier et al (1999). Purified NF (10 27 M) was prepared from a 10 23 M stock (diluted in CH 3 CN) in PS buffer (7 g of Na 2 PO 4 , 5 g of NaCl, and 3 g of KH 2 PO 4 per liter, pH 7) and applied to the entire roots without touching them.…”
Section: Generation Of Transgenic M Truncatula Rootsmentioning
confidence: 99%
“…Infection with Sinorhizobium meliloti wild-type strain Rm2011 was performed as described previously (Schenkluhn et al, 2010). S. meliloti NFs were isolated from a NF-overproducing strain of S. meliloti strain 1021 p(EK327) as described by Baier et al (1999). Purified NF (10 27 M) was prepared from a 10 23 M stock (diluted in CH 3 CN) in PS buffer (7 g of Na 2 PO 4 , 5 g of NaCl, and 3 g of KH 2 PO 4 per liter, pH 7) and applied to the entire roots without touching them.…”
Section: Generation Of Transgenic M Truncatula Rootsmentioning
confidence: 99%
“…Purified chitooligosaccharides were able to induce various defense responses in plants or cultured cells, such as induction of defense-related genes, synthesis of phytoalexin, production of reactive oxygen species, and protein phosphorylation (Felix et al, 1993;Baier et al, 1999;Peck et al, 2001;Shibuya and Minami, 2001;Ramonell et al, 2005). Gene expression profiling studies also demonstrated that chitooligosaccharides can induce a large number of genes (including many defense-related genes) in different plant species (Day et al, 2002;Ramonell et al, 2002Ramonell et al, , 2005.…”
Section: Introductionmentioning
confidence: 98%
“…Preparation and Sources of the Elicitors-The YE was prepared essentially as described (20). Briefly, bakers' yeast (250 g) was dissolved in 500 ml of citrate buffer (20 mM citrate, pH 7.5) by stirring at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture Handling and Treatment-Suspension cultures were prepared from callus derived from alfalfa roots (Medicago sativa L.) and maintained as described (20). Log phase cells were used 3-4 days after a weekly 1:3 dilution in fresh medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation